Appropriation as a perspective and topic in the study of religion and spirituality - Annunen, Linda; Utriainen, Terhi 1962- (2023)
Cultural appropriation is a timely topic that has been taking up a lot of space in public discussions. The concept is often applied in heated debates aimed at calling out’ different actors and actions as appropriation, or on the other hand to defend against such accusations. This thematic issue seeks to look at the topic from a broader and more nuanced perspective, asking what different expressions of appropriation appear in the field of and in relation to religion and spirituality. What discourses and discussions emerge around instances of religious and spiritual appropriation? And how is appropriation understood, negotiated or problematized within, across and around different religious and spiritual groups? The publication is part of the research project ‘Learning from Religion and Spirituality’ (Academy of Finland 2019-2023) [325148].
Keywords: Appropriation; Learning; Majority; Minority; Religion; Religious Change; Ritual; Spirituality